Removing hydrogen solfide (H2S) in biogas with out-column aeration - FANG Shi; CHEN Guo-xi; WU Yu-xiang; FENG Xiao-shan (浙江大学学报. 农业与生命科学版, 2000)
The article presented a new process of removing H2S in biogass by supplying oxygen with circulating medium in an out-coloum aertion reactor with the aim of desulfurization sludge enriched and cultured under certain thiosulfate solution. When the H2S concentration in biogass was 1.1 g/m3 and the feed rate was 0.34 L/min, the removal rate of H2S was then observed to be higher than 98.6%, and the maximum H2S loading was 15.9 mmol·L-1·d-1. When the H2S concentration in biogas was 2.44 g/m3 and the feed rate was 0.17 L/min, the removal rate of H2S and maxium H2S loading were 100% and 17.6 mmol·L-1·d-1 respectively. The optimum pH value was maintained constant at 1.9-2.0 level. Oxygen residual in the outlet gas from the reator was estimated at 0.56 g/m3, which was far below the national standard. In addition, the process system had strong buffering ability for upset state and serious impact caused by irregular changes of H2S loading.